2017
DOI: 10.21767/2574-2825.100028
|View full text |Cite
|
Sign up to set email alerts
|

Consequences and Control Measures of Workplace Violence among Nurses

Abstract: Background: The exposure to violence at workplace can result in post-traumatic stress disorder symptoms, anger, anxiety, shame, guilt, and self-blame among nurses. Workplace violence is associated with nurse absenteeism, medical errors, decreased job satisfaction and burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…This finding is supported by Natarajan et al 15 and Higazee and Rayan 34 and it can be interpreted to mean that student dissatisfaction manifests as carelessness and poor performance. This can lead to poor teacher-student relationship and student perceptions of the superiority of teaching staff with regard to student evaluation.…”
Section: Discussionsupporting
confidence: 55%
“…This finding is supported by Natarajan et al 15 and Higazee and Rayan 34 and it can be interpreted to mean that student dissatisfaction manifests as carelessness and poor performance. This can lead to poor teacher-student relationship and student perceptions of the superiority of teaching staff with regard to student evaluation.…”
Section: Discussionsupporting
confidence: 55%
“…This directs a need for taking definite actions to control violence at the workplace. In the same way with Higazee and Rayan (2017) found that study subjects reported "No" changes at workplace to decrease violence.…”
Section: Has Their Hospital Manger Been Developed Specific Policies Osupporting
confidence: 63%
“…Among these, some reviews have focused on descriptive studies to identify the magnitude and characteristics of workplace violence, as well as its consequences on individuals and healthcare organizations [ 1 , 5 , 12 ]. Individual studies have assessed strategies to manage aggressive patients, as well as consequences of workplace violence, such as nurse absenteeism and job dissatisfaction [ 8 , 13 ]. The aim of this systematic review is to fill an existing gap by identifying studies, which propose effective interventions to help mitigate or prevent workplace violence against nurses.…”
Section: Introductionmentioning
confidence: 99%